Thermal conductivity of solid parahydrogen with methane admixtures - Krivchikov, A.I.; Sumarokov, V.V.; Mucha, J.; Stachowiak, P.; Jezowski, A.; Korolyuk, O.A. (Физика низких температур, 2003)
The thermal conductivity of solid parahydrogen crystal with methane admixtures has been measured in the temperature range 1.5 to 8 K. Solid samples were grown from the gas mixture at 13 K. Concentration of CH₄ admixture molecules in the gas varied from 5 to 570 ppm. A very broad maximum of thermal conductivity with absolute value of about 110 W/(m×K) is observed at 2.6 K. The data are interpreted by Callaway model considering phonons resonant scattering on quasi-local vibrations of CH₄ molecules, phonon-grain boundary and phonon-phonon scattering processes. The increase of grain boundary scattering leads to the decrease of the maximum broadening. The analysis shows that the solid mixture of p-H₂ and CH₄ is a heterogeneous solution for CH₄ concentration higher than 0.1 ppm.